Natural Capital, Ecological Scarcity and Rural Poverty - Barbier, Edward B. (World Bank, Washington, DC, 2013)
Much of the rural poor -- who are growing in number -- are concentrated in ecologically fragile and remote areas. The key ecological scarcity problem facing such poor households is a vicious cycle of declining livelihoods, increased ecological degradation and loss of resource commons, and declining ecosystem services on which the poor depend. In addition, developing economies with high concentrations of their populations on fragile lands and in remote areas not only display high rates of rural poverty, but also are some of the poorest countries in the world today. Policies to eradicate poverty therefore need to be targeted at the poor where they live, especially the rural poor clustered in fragile environments and remote areas. The specific elements of such a strategy include involving the poor in payment for ecosystem services schemes and other measures that enhance the environments on which the poor depend; targeting investments directly to improving the livelihoods of the rural poor, thus reducing their dependence on exploiting environmental resources; tackling the lack of access of the rural poor in less favored areas to well-functioning and affordable markets for credit, insurance, and land; and reducing the high transportation and transaction costs that prohibit the poorest households in remote areas from engaging in off-farm employment and limit smallholder participation in national and global markets.